1999
DOI: 10.1258/0956462991914131
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria Gonorrhoeae in Newcastle upon Tyne 1995-1997: Increase in Ciprofloxacin Resistance

Abstract: Fluoroquinolones and third generation cephalosporins are the most effective antimicrobial agents for the treatment of gonorrhoea. However, clinically significant resistance to fluoroquinolones in Neisseria gonorrhoeae has been reported worldwide including Britain. The aim of this analysis was to study the factors relating to ciprofloxacin resistance and treatment failure. A total of 201 patients attending the Newcastle Genitourinary Medicine (GUM) clinic from 1995-1997 who were diagnosed with culture positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Opa-typing revealed that most isolates from geographically separate locations around the country were distinguishable, as would be anticipated for strains with no recent epidemiological links. A high proportion of the strains with unique opa-types were known to be acquired abroad, particularly from the Far East, which is consistent with the epidemiology of ciprofloxacin-resistant strains isolated in the United Kingdom over previous years [14,15]. However, the cluster of opa-type 1 isolates observed in the North of England is consistent with an emerging trend towards the endemic spread of ciprofloxacin-resistant N. gonorrhoeae [16].…”
Section: Discussionsupporting
confidence: 72%
“…Opa-typing revealed that most isolates from geographically separate locations around the country were distinguishable, as would be anticipated for strains with no recent epidemiological links. A high proportion of the strains with unique opa-types were known to be acquired abroad, particularly from the Far East, which is consistent with the epidemiology of ciprofloxacin-resistant strains isolated in the United Kingdom over previous years [14,15]. However, the cluster of opa-type 1 isolates observed in the North of England is consistent with an emerging trend towards the endemic spread of ciprofloxacin-resistant N. gonorrhoeae [16].…”
Section: Discussionsupporting
confidence: 72%
“…In many GUM clinics empiric cipro¯oxacin therapy is still retained for treatment of infections thought to have been acquired within the UK, but with alternative therapies such as spectinomycin and ceftriaxone being reserved for infections thought to have been acquired from the Far East 24,25 . However, in Liverpool our endemic opatype 1 strain of cipro¯oxacin-resistant N. gonorrhoeae is characterized by being clinically resistant to cipro¯oxacin (MIC range 0.75± 432.0 mg/L, median MIC 12 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options for this group are limited. Already a clinically significant resistance to third generation cephalosporins used in the treatment of gonorrhoea and other sexually transmitted diseases has been reported worldwide [3–5]. This is of particular relevance when considering GM crops that carry the bla TEM gene from which cephalosporin resistance has evolved.…”
Section: Introductionmentioning
confidence: 99%